Tinjauan Victimologis Tentang Peranan Korban Terkait Terjadinya Pengancaman dan Penyebaran Video Call Sex Dalam Hubungan Berpacaran - Yayu Mederlin Nenotek; Aksi Sinurat; Heryanto Amalo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to find out and analyze a victimological review of the victim's role related to the threat and spread of video call sex in dating relationships. This research is a research supported by an approach using primary data in the form of interviews and secondary data in the form of books, legislation, the internet, dictionaries, articles or newspapers obtained using the interview method and document studies, the data that has been collected is processed and analyzed using coding, processing and cleaning techniques and analyzed in a qualitative descriptive manner in describing the results of the research. The results of the study show that (1) The occurrence of VCS in dating relationships does not only occur due to the will of the perpetrator, but there is also a role of the victim in it (2) Legal protection efforts are given to VCS victims, namely legal aid, health assistance and the provision of rehabilitation.